(untitled) (Theatrum historiae, 2017)
This paper addresses the topic of the early modern Habsburg-Ottoman relationship through the special aspect of interpreting and translating in a multicultural environment at the Sublime Porte. More precisely, it focuses on interpreters – in Ottoman context the so called “dragomans” – of the mid- eventeenthcentury Habsburg embassy in Constantinople: Josephus Barbatus, Giovanni Battista Corel and Nicusio Panaiotti. The analysis of their activity as imperial interpreters gives a solid overview of the professional abilities, competences and personal characteristics which were advantageous or disadvantageous for this position; furthermore, it also sheds light upon the various requirements and selection criteria of the imperial government towards interpreters. The paper also reflects investigations concerning the efforts of the Habsburg Court in Vienna in order to create a corps of loyal and competent professional interpreters trained in Constantinople especially for acquiring the necessary skills of Oriental languages in the mentioned period.